Помогите решить тренажер по алгебре пожалуйста!!!!!!!!!! (х-0,2)+(4х-3)=8; (х+0,5)-(2х-3)=9;(2х+0,3)-(3х-3)=5; 2(х-3)-5(х-7)=5-(х+6); 3(х-1)-2(х-6)=4-(х+3); 2(2х-3)-3(7-5х)=4+(2-х); 3(2х-1)-2(6-3х)=5+(4-х):

1

Ответы и объяснения

2013-11-04T17:17:35+00:00
(х-0,2)+(4х-3)=8;
 х -0,2 +4х -3 = 8
5х = 8 +0,2 +3
5х =  4,6
х  = 0,92

 
(х+0,5)-(2х-3)=9;
 х +0,5 -2 х +3 = 9
 - х = 9  -0,5 -3
 -х =  5,5
   х = -5,5

(2х+0,3)-(3х-3)=5;
2х +0,3 - 3х + 3 = 5
5х = 5 -0,3 -3
5х = 1,7
 х = 0,34

2(х-3)-5(х-7)=5-(х+6)
2х -6 -5х +35 = 5 - х -6
2х -5х +х = 5 - 6 +6 -35
-2х =  -30
  х = 15

3(х-1)-2(х-6)=4-(х+3)
3х -3 -2х + 12 = 4 - х -3
3х -2х +х = 4 -3 +3 -12
2х =  -8 
х = -4

 2(2х-3)-3(7-5х)=4+(2-х); 
4х -6 -21 +15х = 4 +2 -х
4х +15х +х = 4 + 2 +6 +21
19х = 33
 х =  1,73

3(2х-1)-2(6-3х)=5+(4-х):
6х -3 - 12 +6х = 5 +4 -х
6х +6х +х = 5+ 4 +3 + 12
13х = 24
х =  1,84